An Internal Control for Evaluating Bisulfite Conversion in the Analysis of Short Stature Homeobox 2 Methylation in Lung Cancer - Lan, Vo Thi Thuong (Asian Pac J Cancer Prev, 2019)
OBJECTIVE: The methylation status is considered as powerful diagnostic, prognostic, and predictive biomarkers. However, the limited DNA amount and conversion efficiency after bisulfite treatment are considerable hindrances in quantitative methylation analysis. In this study, we designed an artificial internal control (IC) system that contained the cytosine-free fragment (CFF) following CpG sequences of the SHOX2 promoter whose methylation status has been described as a valuable biomarker of lung cancer. Its performance in quantifying DNA recovery and bisulfite conversion efficiency as well as in detecting false-positive SHOX2 methylation was determined on samples from lung cancer patients. MATERIAL AND METHODS: The IC system is composed of two pConIC and pUnIC plasmids that both contain a cytosine-free (CF) sequence derived from the CFF and the CpG containing SHOX2 sequences. They are identical in sequence, except that in the ConIC insert, all cytosines have been converted into thymines. Thus, the ConIC can be used as calibrator of 100% bisulfite conversion efficiency, while the UnIC is the indicator in order to evaluate the DNA recovery, bisulfite conversion efficiency of the SHOX2 promoter sequence by quantitative real time PCR. RESULTS: The copy number of the target sequences impacted on both DNA recovery rates and bisulfite conversion efficiency. An amount of 0.005 ng pUnIC (10(6) copies) showed recovery rate of 18%, similar to that of pConIC, and a bisulfite conversion efficiency of the SHOX2 reaching 98.7%. On the contrary, higher copy number of pUnIC showed incomplete conversion (<85%) and over recovery (~42%). Using this calibrator/indicator couple, we were able to detect false-positive SHOX2 methylation (3.77% instead of 0.03%) due to incomplete bisulfite conversion. CONCLUSION: Our results proposed a customizable internal control using the ConIC/UnIC as calibrator/indicator to quantify simultaneously and accurately the DNA recovery and bisulfite conversion efficiencies of individual sequence as well as whole genome in methylation assays, thus promoting the validation of standardized clinical DNA methylation biomarker values to progress toward clinical applications.